On the computational complexity of curing non-stoquastic Hamiltonians - Marvian, Milad; Lidar, Daniel A.; Hen, Itay (Nature communications, 2019)
Quantum many-body systems whose Hamiltonians are non-stoquastic, i.e., have positive off-diagonal matrix elements in a given basis, are known to pose severe limitations on the efficiency of Quantum Monte Carlo algorithms designed to simulate them, due to the infamous sign problem. We study the computational complexity associated with ‘curing’ non-stoquastic Hamiltonians, i.e., transforming them into sign-problem-free ones. We prove that if such transformations are limited to single-qubit Clifford group elements or general single-qubit orthogonal matrices, finding the curing transformation is NP-complete. We discuss the implications of this result. Non-stoquastic Hamiltonians are known to be hard to simulate due to the infamous sign problem. Here, the authors study the computational complexity of transforming such Hamiltonians into stoquastic ones and prove that the task is NP-complete even for the simplest class of transformations.